Factors of Airline Selection and Reflight Intention During the Pandemic/Case of Serbian Airlines Users - Aleksić, Milica; Popov Raljić, Jovanka; Gajić, Tamara; Blešić, Ivana; Dragosavac, Miloš; Penić, Mirjana; Bugarčić, Jovan (Frontiers in Psychology, 2022)
The global pandemic coronavirus disease 2019 (COVID-19) has caused significant economic changes for all segments of the economy. Travel restrictions have landed several commercial airlines and significantly reduced their revenues. Safety measures are strict and very demanded, especially when it comes to food drinks and beverages served during flights. This article aims to discover the predictors that influenced the intention of the airline’s passengers to travel long-distance flights in unusual conditions of the COVID-19 pandemic and differs from current studies on airline selection and passenger loyalty because it includes changes in the behavior of employees who regularly fly medium- and long-distance flights. Requirements for passenger’s airline selection have been changed, which is why this study aimed to determine which factors influence the selection during reopening after lockdown. Determinants of food quality and safety during flights are a long-term challenge and could affect passengers’ choice of the airline they want to fly. This study was conducted during the reopening period of airlines, during the COVID-19 pandemic, on a sample of 369 Serbian passengers and employees on medium- and long-distance flights, in the period from November 20, 2020 to January 15, 2021. Regression analysis concluded that certain predictors such as food service quality and safety significantly affect the attitude, subjective norms, and perceived behavioral control (PBC) of passengers and trigger the intention that affects behaviors in the choice of the airline during the COVID-19 pandemic, especially when it comes to the flights with medium and long durations. To better interpret the effects, a path analysis was performed in the SPSS Analysis of Moment Structures (AMOS) software, version 26.00 with the aim to examine the importance and significance of causal relationships between groups of variables. The results confirmed the theory of planned behavior; that intentions are a significant mediator between the mentioned independent variables (attitudes about quality and safety of food, drinks and beverages, subjective norms, and perceived behavior control) and passenger behavior when rechoosing the same airline.